The efficacy of therapy with DPP-4 inhibitors combined with insulin in patients with type 2 diabetes mellitus - Alexander Sergeevich Ametov; Ekaterina Vladimirovna Karpova (Сахарный диабет)
Recently, researchers started to pay increasingly more attention to the role of gastrointestinal hormones in regulation of insulin secretion, i.e. glucosehomeostasis. To-day, there are two approaches to the treatment of DM based on the use of GLP-1 effects. One takes advantage of DPP-4 inhibitorsthe other is combination of these agents with various drugs necessitated by heterogeneity of pathophysiological factors responsible for the developmentof DM2. The latter approach ensures multiple therapeutic effects on DM2 and its complications. Many on-going studies are focused on the use ofcombination of DPP-4 inhibitors and insulin. Vildagliptin (Galvus, Novartis Pharma, Switzerland) is presently the sole DPP-4 inhibitor approvedfor application with insulin in Russia.Aim. To estimate the efficacy and safety of DPP-4 inhibitor combined with long-acting insulin in the treatment of DM2. Materials and methods. The study group included 18 patients (2 men and 16 women) with DM2 treated with long-acting insulin (glargine, humulinNPH) for at least 3 months at a mean daily dose of 31.96?4.95 U. The age of the patients averaged 59.9?2.84 years (46-75), DM2 duration8.9?1.18 years (2-15). Parameters of comprehensive glycemic control (FG, PPG, HbA1c, LMWH - low-molecular weight heparins CGM-continuousglucose monitoring) were measured using a CGMS system in the beginning and end of the study. Functional activity of pancreatic betbeta-cells and insulinresistance (HOMA-IR), lipid metabolism, and anthropometric characteristics were estimated. Results. Combined therapy resulted in positive dynamics of carbohydrate metabolism within 12 weeks after onset. The functional activity of pancreaticbetbeta-cells significantly (by 157.96 U) improved by the end of the study. Changes of HOMA-IR were insignificant. CGM showed that prescription ofvildagliptin to the patients who failed to reach compensation of DM2 with long-acting insulin alone significantly improved glycemic control. Variabilityof glycemia remained unaltered during the entire period. Conclusion. Combined therapy of DM2 patients with vildagliptin and long-acting insulin for 12 weeks improved parameters of carbohydrate metabolismwithout hypoglycemic episodes changes, in fluctuation amplitude and body weight. The functional activity of pancreatic betbeta-cells was likewiseimproved.